PELATIHAN MANAJEMEN BENGKEL/LABORATORIUM BAGI GURU MATA PELAJARAN PRAKTIK DI SMK WILAYAH KABUPATEN PANDEGLANG - Iik Nurulpaik; Hasbullah Hasbullah; Wawan Purmana; Neris Peri Ardiansyah (Universitas Widyatama, 2020)
The function of the workshop/laboratory management in Vocational High Schools has not been fully utilized, it is only limited to the use of student practicum places and has not been widely used by managers in improving the quality of workshops/laboratories in schools. The management of workshop/laboratory facilities is very important in improving the quality of teachers and students in meeting the quality of learning and the results of the quality of learning in order to improve the quality of graduates. Vocational High Schools are basically not only intended to understand theoretical mastery but must also have theoretical and practical competence in meeting performance criteria. Thus the teacher has a very important role in mastering and managing the workshop. Workshop / Laboratory Management Training for Practical Subject Teachers at SMK Pandeglang Regency is carried out to improve teacher management in managing workshop/laboratory facilities at SMK.